Boosting Religious Belief During the Pandemic Era in Sukaraya Village 2021 - Sarah Dina; Rahmi Gustina Matondang; Meidini Mutia; Fahmi Sahil; Franindya Purwaningtyas (International Journal Labs, 2021)
This research is motivated by the crisis crisis that befell the people of Sukaraya village. The outbreak of the Covid-19 virus has become a global problem that infects hundreds to thousands of people in the world. Most of the international community experienced depression and mental shock. This condition without causing anxiety, panic and even stress. The presence of the concept of a faith supplement in the heart has a major role in tackling various spiritual problems that arose during the Covid-19 pandemic. This study aims to renew and improve the supplement of faith in the heart during the Covid-19 pandemic in the village. Sukaraya, District. Stone Shower, Kab. Deli Serdang. The research method used is qualitative, qualitative data obtained by face-to-face interview techniques. This study also uses a systematic procedural approach. The results of this study indicate that efforts to increase faith supplements in the heart during the Covid-19 pandemic in the village. Sukaraya needs to be done to avoid excessive anxiety. In addition, the public really appreciates and acknowledges the existence of the Covid-19 virus that has hit Indonesia. However, the public must also acknowledge the existence of the creator of the virus. The momentum of the Covid- 19 virus should be used as an opportunity to get closer to the creator. Allah SWT, by worshiping. Devoutly and trusting in Him.